Transrealism: in pursuit of social change and collective justice in Huxley's Brave New World - Nadernia, Vafa (Penerbit Universiti Kebangsaan Malaysia, 2018)
Science fiction stories extend the limits of human realities. In that imagined world where things appear different, mysterious, and normless, human measures such as sexism, prejudice, viciousness and other judicial realms are negotiated through atypical lenses. Therefore, what remains noticeable here would be the question if science fiction is an agent for social change and collective justice and decent mortalities. The main purpose of this article is to argue how Rudy Rucker's Transrealism -works as an interplay between dream and reality in which the writer shapes his/her own immediate perceptions in a fantastic way- can carry out this commitment. The selected text of analysis here will be Aldous Leonard Huxley' Brave New World (1932), which will be theoretically analyzed based on the doctrine of UN Social Justice in an Open World: The Role of the United Nations (2006) published under the auspices of the Department of Economic and Social Affairs of the United Nations Secretariat. The main elements of UN document will be the Six important areas of inequality in the distribution of goods, opportunities and rights. The implication of the present inquiry would depict the role of science fiction novels, such as Huxley's Brave New World, to challenge today's human position in the world, to call for social values for a better community to exist and to restore social justice as a milestone for a fair new world to live in.